Scheduling of Products for Reconfiguration Effort in Reconfigurable Manufacturing System. (2018) - Prasad, Durga; Jayswal, S.C.
Abstract: Reconfigurable manufacturing system is a responsive manufacturing system which can easily adjust its capacity and functionality with least effort and time when demand of the product changes. Reconfigurable manufacturing system (RMS) has the exactly capacity and functionality whenever is required. In the present work a methodology has been presented for scheduling of the products on the basis of reconfiguration effort in a multi-product line. For scheduling of products, three criteria have been considered; reconfiguration effort, profit over cost and due date. Integrated approach of Shannon entropy and TOPSIS has been used for scheduling of the products.